What to Sell and How to Sell Matters: Focusing on Luxury Hotel Properties' Business Performance and Efficiency. (February 2022) - Kim, Jaewook; Kim, Sung In; Lee, Minwoo
Due to service product characteristics and a mix of complex sales, it is crucial for hotel firms to efficiently design limited physical spaces that serve multiple purposes to optimize revenue and maximize profit. Since luxury hotel properties have different operation strategies than limited-service hotels, their operational efficiency should be a reference during strategic decision-making processes. Primary research purpose is to identify the most efficient operation model for luxury hotel properties. The study computed operation efficiency scores using the data envelopment analysis approach to rank the property efficiency of 37 fully equipped luxury hotels in the United States. Each property can utilize slack analysis to discover a strategic benchmarking company (best efficient frontier) and intuitive strategic recommendations and gain superior input and output productivity. Tobit model analysis provides supplemental understandings regarding the additional operational factors impacting luxury hotel properties' efficiency score variations. Operating efficiency was found to be achieved by multiple operating inputs and influenced by relative price, fixed costs, and management systems. Theoretical comprehensiveness of luxury service mix has been empirically tested by highlighting efficiency as a key measure. In addition, RevPAR's ratio on TRevPAR further highlights the importance for luxury hotels to increase non-room sales and revenues to accomplish efficiency.